Biosorption Mechanism of Aqueous Pb2+, Cd2+, and Ni2+ Ions on Extracellular Polymeric Substances (EPS). (24th June 2020) - Cui, Di; Tan, Chong; Deng, Hongna; Gu, Xunxue; Pi, Shanshan; Chen, Ting; Zhou, Lu; Li, Ang
Abstract : Heavy metal pollution has been a focus with increasing attention, especially Pb 2+, Cd 2+, and Ni 2+ in an aqueous environment. The adsorption capacity and mechanism of extracellular polymeric substances (EPS) from Agrobacterium tumefaciens F2 for three heavy metals were investigated in this study. The adsorption efficiency of 94.67%, 94.41%, and 77.95% were achieved for Pb 2+, Cd 2+, and Ni 2+ adsorption on EPS, respectively. The experimental data of adsorption could be well fitted by Langmuir, Freundlich, Dubinin–Radushkevich isotherm models, and pseudo-second-order kinetic model. Model parameters analysis demonstrated the great adsorption efficiency of EPS, especially for Pb 2+, and chemisorption was the rate-limiting step during the adsorption process. The functional groups of C=O of carboxyl and C-O-C from sugar derivatives in EPS played the major role in the adsorption process judged by FTIR. In addition, 3D-EEM spectra indicated that tyrosine also assisted EPS adsorption for three heavy metals. But EPS from strain F2 used the almost identical adsorption mechanism for three kinds of divalent ions of heavy metals, so the adsorption efficiency difference of Pb 2+, Cd 2+, and Ni 2+ on EPS could be correlated to the inherent characteristics of each heavy metal. This study gave the evidence that EPS has a great application potential as a bioadsorbent in the treatment of heavy metals pollution.